A case of Weil's disease presenting as Stevens-Johnson syndrome. (April 2022) - Payra, Biswajit; Aggarwal, Ramesh; Ghotekar, L H; Islam, Sheikh Yasir; Kumar, Pradeep; Sidharth, S
Leptospirosis presents in a biphasic manner: an early leptospiraemic phase and a late immune phase. In its severe form, it presents with multi-organ failure, also known as Weil's disease. Stevens-Johnson syndrome (SJS) is an autoimmune hypersensitive reaction leading to diffuse fluid filled vesicle formation with detachment of skin and mucous membrane. Though SJS is triggered by different infections and drugs, its association with leptospirosis is not frequently reported. Here we present such a case.